1991
DOI: 10.1099/0022-1317-72-9-2105
|View full text |Cite
|
Sign up to set email alerts
|

Typing of hepatitis C virus genomes by restriction fragment length polymorphism

Abstract: Recently, we reported that hepatitis C virus (HCV) can be classified genetically into two types, HCV-K1 and HCV-K2, which show 67% and 71% identity at the nucleotide and amino acid sequence levels in a 340 bp region which encodes the NS5 gene Gly-Asp-Asp motif. To develop a rapid method to classify the genomes of HCV isolates, we identified restriction fragment length polymorphisms (RFLPs) in reverse transcriptase-polymerase chain reaction products encoding a portion of the NS5 gene. AluI and AccII enabled HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
2
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(91 citation statements)
references
References 26 publications
5
83
2
1
Order By: Relevance
“…Previous work has demonstrated that all six currently defined major genotypes of HCV (Simmonds et al, 1993a;Bukh et al, 1993) can be distinguished on the basis of RFLP analysis of RT-PCR products derived from the 5'NCR (Nakao et al, 1991;McOmish et al, 1993McOmish et al, , 1994Simmonds et al, 1994b). In one previous study, amplified DNA is cleaved with HaeIII-RsaI in one reaction and with MvaI-HinfI in a second, and the virus genotype is deduced by the combination of electropherotypes produced .…”
Section: Predicted Electropherotypes Of Published Hc V 5"ncr Sequencementioning
confidence: 99%
“…Previous work has demonstrated that all six currently defined major genotypes of HCV (Simmonds et al, 1993a;Bukh et al, 1993) can be distinguished on the basis of RFLP analysis of RT-PCR products derived from the 5'NCR (Nakao et al, 1991;McOmish et al, 1993McOmish et al, , 1994Simmonds et al, 1994b). In one previous study, amplified DNA is cleaved with HaeIII-RsaI in one reaction and with MvaI-HinfI in a second, and the virus genotype is deduced by the combination of electropherotypes produced .…”
Section: Predicted Electropherotypes Of Published Hc V 5"ncr Sequencementioning
confidence: 99%
“…6 In clinical practice, HCV can be genotyped by direct sequence analysis, by reverse hybridization to genotype-specific oligonucleotide probes, or by restriction fragment length polymorphism analysis. [29][30][31] Two standardized kits based on PCR amplification of the 5' noncoding region are commercially available. The Trugene HCV 5'NC Genotyping kit (Visible Genetics, Toronto, Ontario, Canada) 32,33 is based on direct sequencing of PCR amplicons and sequence comparison with a reference sequence database.…”
Section: Direct Testsmentioning
confidence: 99%
“…RFLP analysis of 5 0 UTR was employed by Nakao et al [13] making use of the conserved type-specific point mutations in the 5 0 UTR. Okamoto et al [14] designed type-specific primers from the core region of HCV to develop a nested PCR method for genotyping.…”
mentioning
confidence: 99%